Self-directed learning and approach to seeking medical evidence: perceptions of students from a private medical university of Karachi - Naseem Amin Dhedhi; Faisal Ahmed; Bushra Rabbani; Syed Muhammad Zulfiqar Hyder Naqvi (Journal of the Pakistan Medical Association, 2023)
Objective: To assess self-directed learning among medical students and their approach towards seeking medical evidence. Method: The cross-sectional study was conducted from November 30, 2021, to June 30, 2022, at the Baqai Medical University, Karachi, and comprised first to fifth year medical students of either gender. Data was collected using a structured online questionnaire which also included questions from the self-directed learning instrument. Data was analysed using SPSS 21. Results: Of the 250 students approached, 159(63.6%) responded were received; 102(64.2%) females and 57(35.8%) males. The overall mean age was 21.78±1.72 years, with 88(54.1%) subjects aged >21 years. Majority 127(79.9%) participants scored above average on the self-directed learning instrument scale, while 131(84.2%) showed satisfactory approach towards evidence-based medicine. Students with better attitude towards self-directed learning were more likely to have satisfactory approach towards evidence-based medicine, but this relationship was not significant (p=0.136). Conclusion: Medical students were found to be keen to adopt self-directed learning and practice evidence-based medicine though they have not been formally exposed to it. Key Words: Evidence-based medicine, self-directed learning as topic, Students, Medical.